PENGARUH MERK DAGANG DAN STRATEGI HARGA TERHADAP MINAT BELI KONSUMEN PADA PRODUK GADGET MERK APPLE - HENDRA . (JURNAL ILMIAH SIMANTEK, 2019)
This study aim to analyze the influenze of Brand and Price Strategy on Consumer Buy Interest of Gadget Product Apple’s Brand. Research variable include : Consumer Buy Interest (Y) as the dependent variable, Brand (X1) as the independent variable, and Price Strategy (X2) as the independent variable. This study adopted the Marketing Management theory, as it pertaining to the Brand, Price Strategy, and Consumer Buy Interest. This research applies a survey approach with a descriptive and qualitative method and uses an explanation power as it characteristics. The method of collecting the data is done by using interview, questionaires, and documentation study. The method of data analysis used is the multiple regression analysis and the simple regression analysis. The population number is unknown and sample search using the limeshow formula as many as 96 people The first hypotesis finding shows the brand influences significantly on the Consumer Buy Interest of Gadget Product Apple’s Brand The second hypotesis shows that Price Strategy influences significantly on the Consumer Buy Interest of Gadget Product Apple’s Brand The third hypotesis shows that the Brand and Price Strategy simultaneously influence significantly on the Consumer Buy Interest of Gadget Product Apple’s Brand In partial, the Price Strategy variable shows more dominantly than the Brand of Gadget Product Apple’s. This means that the Consumer Buy Interest of Brand of Gadget Product Apple’s are influenced highly by the Price Strategy and it is the Price Strategy that gives mostly.